Perkembangan Bahasa Aud Dan Praktek Permainan Bahasa Anak - Suhartining; Winda Fauzia; Ramadha Tsulatsi Hajar (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
Language is the only communication tool for children to convey what they feel. Early Childhood Education develops six aspects of children's learning, namely Religious and Moral Values, Social Emotional, Language, Cognitive, Physical Motoric and Art. Language development aspects become the main focus on writing In this article. Games cannot be separated from the world of children. Because by playing children can express their feelings in various models of children's language. Interesting games with various shapes, colors and sounds will make children happy to play them. There are various forms of games language for children such as traditional games, finger puppets, face guessing, storytelling and magic box games. The research method used is a literature review taken from several articles on language development and the practice of children's language games. The purpose of writing this article is for teachers to stimulate language development children with a variety of fun game models an. That way children can be separated from dependence on gadgets.